Liderança e comprometimento: uma relação possível? - Bassan, Jaqueline Santa Lucia (2007)
The subject of this research brings a problem linked with a theoretical model about leadership developed by Likert (1975), and with a theoretical model of organizational commitment by Allen and Meyer (1990, 1991, 1997). The maintenance of a high standard of performance requires flexibility, innovation and agility, characteristics necessary to the maintenance of the competitive advantage, and which are caused basically by the resources and the internal capacity of each organization. Since the bosses are, most times, responsible for the development of a capable and commited work force, their action is of key importance, and the professionals dedicated to the field of people´s management need to be constantly interested in finding out the reasons which take the worker to commit himself/herself to the organization effectively and efficiently. In this sense, when identifying the bosses´s leadership styles of each sector/unit/department on an operational level of a hospital institution in Santa Maria RS and the kinds of commitment (affective, normative or calculative) of its workers, the descriptive study aimed at verifying if there is any relation between the bosses´s leadership style and the kind of commitment of the worker. This study showed that the predominant leadership style in the 37 sectors/units/departments which were researched was the Consultive and/or Participative. Such styles characterize the leadership of 35 bosses, and the Benevolent Authoritarian style appears in only 2 sectors of the researched bosses. Likewise, the research pointed out the kind of commitment of the workers, in each sector/unit/department, to the organization being studied. In 12 sectors the interviewees are affectively commited. In 6 sectors the interviewees are affective-normatively commited. In 1 sector the interviewees are commited affectively and calculatively. In 18 sectors the interviewees are commited not only affectively and normatively, but also in a calculative way. Relating the leadership styles presented by the bosses of the organization being studied and the nature of the worker´s commitment to it, it is possible to conclude that the results do not allow to state that the leadership styles are responsible for the nature of the commitment, since there are a lot of kinds of commitment for the same leadership style. Such iversification of behavioral standards signals the existence of (an)other component(s) which determine(s) the nature of the commitment. It is important to highlight that even though this research does not show a direct relation between leadership and commitment, its findings allow to conclude that the leadership style cannot be analysed as an independent actor, since it is the reflection of the organization culture